Findings from Waves 1 to 4: Special Topics - Wooden, Mark; Killackey, Eion; Johnson, Guy; Scutella, Rosanna; Chigavazira, Abraham; Moschion, Julie (Melbourne Institute of Applied Economic and Social Research, 2014)
This research report presents important findings from the first four waves of the JH study, which were conducted over an 18-month period between September 2011 and May 2013. The report is structured into eight chapters, five of which explore, in depth, a key issue affecting the homeless and people facing housing insecurity. The five issues examined are: the duration of homelessness, mental illness, psychological distress, substance use, and links with and between child and adult abuse and violence.
Journeys Home Research Report No. 4
Journeys Home Research Report
Keywords: Homelessness; Health -- Addictive behaviours; Health -- Mental; Health and wellbeing; Housing, communities and neighbourhoods; Homelessness; Health; Addictive behaviours; Mental; Health and wellbeing; Housing, communities and neighbourhoods